2006
DOI: 10.1021/ja0602694
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Versatile Chiral-Bridged Atropisomeric Diphosphine Ligands:  Remarkably Efficient Ligand Syntheses and Their Applications in Highly Enantioselective Hydrogenation Reactions

Abstract: A series of chiral diphosphine ligands denoted as PQ-Phos was prepared by atropdiastereoselective Ullmann coupling and ring-closure reactions. The Ullmann coupling reaction of the biaryl diphosphine dioxides is featured by highly efficient central-to-axial chirality transfer with diastereomeric excess >99%. This substrate-directed diastereomeric biaryl coupling reaction is unprecedented for the preparation of chiral diphosphine dioxides, and our method precludes the tedious resolution procedures usually requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(74 citation statements)
references
References 71 publications
0
73
1
Order By: Relevance
“…9). Chan and coworkers developed a serial of effective diphosphine ligands, such as axially chiral P-Phos [66], PQ-Phos, [67] phosphinite ligands H 8 -BINAPO [68], and Spiropo [69] with high activity and can be immobilized in DMPEG (poly(ethylene glycol) dimethyl ether) for recycling. Reetz's group found that BINOL-derived diphosphonites linked to an achiral diphenyl ether unit were also effective [70].…”
Section: Scheme 18 Asymmetric Hydrogenation Of Quinolines With Water mentioning
confidence: 99%
“…9). Chan and coworkers developed a serial of effective diphosphine ligands, such as axially chiral P-Phos [66], PQ-Phos, [67] phosphinite ligands H 8 -BINAPO [68], and Spiropo [69] with high activity and can be immobilized in DMPEG (poly(ethylene glycol) dimethyl ether) for recycling. Reetz's group found that BINOL-derived diphosphonites linked to an achiral diphenyl ether unit were also effective [70].…”
Section: Scheme 18 Asymmetric Hydrogenation Of Quinolines With Water mentioning
confidence: 99%
“…Since the 1990s, ruthenium-catalyzed reactions such as [16] olefin metathesis [17], the oxidation of alcohols and amines [18], asymmetric reduction using hydrogen [19], hydroamination and hydroaminomethylation of olefins have attracted a great interest in organic synthesis [20]. Among these complexes, half-sandwich ruthenium(II) arenes are important and widely used organometallic compounds and exhibit a diverse range of coordination chemistry [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric hydrogenation of these substrates 2 is the simplest and most direct route to synthesize 1 because of its inherent efficiency and atom economy. In contrast to the great progress in the synthesis of ␤-substituted ␤-amino acids and derivatives via enantioselective hydrogenations (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), reports on the synthesis of ␣-substituted ␤-amino acids with this protocol are very limited. To the best of our knowledge, only one exceptional example has been given, very recently by Zheng and coworkers (38), using Rh-monophosphorus catalyst system for the hydrogenation of ␤-phthalimide acrylates.…”
mentioning
confidence: 99%
“…The results of using Ru-BINAP (56, 57), Bu-PQ-Phos (35,36), and Rh-Monophos (24) complexes as catalysts were rather disappointing, showing poor reactivities and enantioselectivities (Table 1, entries 1-9). Good improvement occurred by employing Rh-(Me-Duphos) (58) or Rh-Tangphos (59) complex in this reaction.…”
mentioning
confidence: 99%